2012
DOI: 10.1093/brain/aws113
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid burden and metabolic function in early-onset Alzheimer's disease: parietal lobe involvement

Abstract: Alzheimer's disease with early onset often presents with a distinct cognitive profile, potentially reflecting a different distribution of underlying neuropathology. The purpose of this study was to examine the relationships between age and both in vivo fibrillary amyloid deposition and glucose metabolism in patients with Alzheimer's disease. Dynamic [(11)C]Pittsburgh compound-B (90 min) and static [(18)F]fluorodeoxyglucose (15 min) scans were obtained in 100 patients with Alzheimer's disease and 20 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 52 publications
11
89
1
Order By: Relevance
“…These clinical variants include posterior cortical atrophy (PCA, 'visual variant of Alzheimer's disease'; Crutch et al, 2012), logopenic variant primary progressive aphasia (logopenic variant PPA, 'language variant of Alzheimer's disease'; Gorno-Tempini et al, 2011), corticobasal syndrome (Alzheimer's disease pathology is the causative pathology in up to 25% of cases; Dickson et al, 2002;Lee et al, 2011), and memorypredominant and behavioural/dysexecutive variants of Alzheimer's disease (Ossenkoppele et al, 2015c). Age at onset has also been associated with clinical and anatomical variability; while patients with late-onset Alzheimer's disease (565 years of age) typically present with amnestic symptoms and medial temporal lobe neurodegeneration, patients with early-onset (565 years) tend to exhibit greater non-amnestic deficits and neocortical-predominant atrophy (Rabinovici et al, 2010;Mendez et al, 2012;Ossenkoppele et al, 2012;Smits et al, 2012;Moller et al, 2013;Cavedo et al, 2014). Furthermore, patients with Alzheimer's disease who carry the apolipoprotein E (APOE) e4 allele have shown greater medial temporal lobe vulnerability (Pievani et al, 2009;van der Flier et al, 2011;Ossenkoppele et al, 2013b;Lehmann et al, 2014) and post-mortem tau pathology (Beffert and Poirier, 1996;Tiraboschi et al, 2004) compared to non-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…These clinical variants include posterior cortical atrophy (PCA, 'visual variant of Alzheimer's disease'; Crutch et al, 2012), logopenic variant primary progressive aphasia (logopenic variant PPA, 'language variant of Alzheimer's disease'; Gorno-Tempini et al, 2011), corticobasal syndrome (Alzheimer's disease pathology is the causative pathology in up to 25% of cases; Dickson et al, 2002;Lee et al, 2011), and memorypredominant and behavioural/dysexecutive variants of Alzheimer's disease (Ossenkoppele et al, 2015c). Age at onset has also been associated with clinical and anatomical variability; while patients with late-onset Alzheimer's disease (565 years of age) typically present with amnestic symptoms and medial temporal lobe neurodegeneration, patients with early-onset (565 years) tend to exhibit greater non-amnestic deficits and neocortical-predominant atrophy (Rabinovici et al, 2010;Mendez et al, 2012;Ossenkoppele et al, 2012;Smits et al, 2012;Moller et al, 2013;Cavedo et al, 2014). Furthermore, patients with Alzheimer's disease who carry the apolipoprotein E (APOE) e4 allele have shown greater medial temporal lobe vulnerability (Pievani et al, 2009;van der Flier et al, 2011;Ossenkoppele et al, 2013b;Lehmann et al, 2014) and post-mortem tau pathology (Beffert and Poirier, 1996;Tiraboschi et al, 2004) compared to non-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…It affects cognition, thought process, learning Early onset of AD is seen in people between 30 and 60 years of age due to inherited genes in an autosomal-dominant manner [15,16] . The younger population with early-onset AD possesses a distinct cognitive profile reflecting different distribution of underlying neuropathology [17] . Ossenkoppele et al [17] observed that increased amyloid-beta (Aβ) deposition in the parietal lobe and metabolic dysfunction contribute to the distinct cognitive profile of patient's with AD.…”
Section: Introductionmentioning
confidence: 99%
“…The younger population with early-onset AD possesses a distinct cognitive profile reflecting different distribution of underlying neuropathology [17] . Ossenkoppele et al [17] observed that increased amyloid-beta (Aβ) deposition in the parietal lobe and metabolic dysfunction contribute to the distinct cognitive profile of patient's with AD.…”
Section: Introductionmentioning
confidence: 99%
“…2). Ossenkoppele et al [15] reported that a greater amyloid burden and modest metabolic dysfunction in the parietal cortex shown in younger AD patients is related to cognitive deficits such as acalculia, spatial disorientation, and apraxia [16]. Importantly, the ε4 allele predisposes to beginning β-amyloid accumulation [17], and to decreasing signals in the parietal association brain areas earlier in life [18].…”
Section: Discussionmentioning
confidence: 99%